Pengembangan Media Pembelajaran Interaktif Berbasis Artificial Intelligence Menggunakan Model ADDIE untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN Umbuldamar - Jammilna Darojat; Hidayat Alam Sudrajat; Devi Ratna Handini (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aimed to develop an Artificial Intelligence (AI)-based interactive learning media using the ADDIE model and to examine its feasibility and effectiveness in improving the learning outcomes of fifth-grade students at SDN Umbuldamar. This research employed a Research and Development (R&D) approach consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 25 fifth-grade students. The research instruments included expert validation sheets (content and media experts), student response questionnaires, and learning achievement tests in the form of pretest and posttest. The validation results indicated a very high level of feasibility, with 92% from content experts and 90% from media experts. The effectiveness test showed an increase in the average student score from 62.4 to 86.8, with an N-Gain score of 0.74 categorized as high. Statistical analysis revealed a significant difference before and after the implementation of the AI-based learning media. Therefore, the developed AI-based interactive learning media is considered feasible and effective in improving elementary students' learning outcomes.